Commissioning for nuclear power plants. (International Atomic Energy Agency, 2014)
"This Safety Guide provides recommendations on the basis of international best practices, as currently followed in IAEA Member States, on how to meet the requirements for the commissioning for nuclear power plants. These requirements enable the commissioning of a nuclear power plant to proceed safely and to a high quality. The recommendations will also enable the necessary assurances to be provided that the plant has been constructed in accordance with the design intent and can be operated safely."--Publisher's description.
"IAEA safety standards for protecting people and the environment"--Cover.
"STI/PUB/1595"--Title page verso.
"May 2014"--Title page verso.
Keywords: Nuclear power plants -- Commissioning.; Nuclear power plants -- Safety measures.; Nuclear fuels -- Safety measures.; elektronické knihy; electronic books